APLIKASI UNDANG-UNDANG TENTANG INFORMASI DAN PELAYANAN PUBLIK DALAM KASUS SISTEM INFORMASI TEKNOLOGI PENGELOLAAN AIR BERSIH DAN LIMBAH CAIR - Komarudin, Komarudin; Yudo, Satmoko (Center for Environmental Technology, 2009)
The Law of Information and Electronics Transaction, the Law of Public Information Transparency, the Law of Ombudsman of the Republic of Indonesia, and the Law of Public ServicesÃ‚Â is a part of the legal system related to information and public services. These four laws should be scrutinized in terms of technology application. To create prime services in the management of clean water and waste water, it has been developed the technology information system of clean water and waste water processing (SITPABLC). SITPABLC is the information system to provide information and technology services due to supporting the implementation of these four laws.Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Keywords: informasi, transaksi elektronik, informasi publik, keterbukaan informasi publik, pelayanan publik, ombudsman, dan good governance.Ã‚Â